Solvability of Some Types for Multi-fractional Integro-Partial Differential Equation (Baghdad Science Journal, 2021)
In this article, the solvability of some proposal types of the multi-fractional integro-partial differential system has been discussed in details by using the concept of abstract Cauchy problem and certain semigroup operators and some necessary and sufficient conditions.